Effects of Driving Pressure-Guided Ventilation on Postoperative Pulmonary Complications in Prone-Positioned Patients Undergoing Spinal Surgery: A Randomized Controlled Clinical Trial. Issue 10 (3rd October 2022) - Jin, Di; Liu, Huayue; Kong, Xiaoqi; Wei, Guangle; Peng, Ke; Cheng, Hao; Ji, Fuhai
Abstract: Background: Prolonged spinal surgery in the prone position may lead to postoperative pulmonary complications (PPCs). We aimed to compare the effects of driving pressure-guided ventilation versus conventional protective ventilation on postoperative pulmonary complications in patients undergoing spinal surgery in the prone position. We hypothesized that driving pressure-guided ventilation would be associated with a decreased incidence of PPC. Methods: We enrolled 78 patients into this single-center, double-blind, randomized controlled trial. The driving pressure (DP) group (n = 40) received a tidal volume of 6 ml/kg of predicted body weight, individualized positive end-expiratory pressure (PEEP) which produced the lowest driving pressure (plateau pressure-PEEP), and a recruitment maneuver. The protective ventilation (PV) group (n = 38) received the same tidal volume and recruitment maneuver but with a fixed PEEP of 5 cm H2 O. Our primary outcome was postoperative pulmonary complications based on Lung Ultrasound Scores (LUS) at the end of the surgery and the simplified Clinical Pulmonary Infection Score (sCPIS) on postoperative days (POD) 1 and 3. Results: DP patients had lower LUS and POD1 sCPIS than the PV group ( p  < 0.01). DP patients had lower driving pressure during the surgery than PV patients ( p  < 0.01). Perioperative arterial blood gases and hemodynamic parameters were comparable between the two groups ( p  > 0.05). The visual pain score (VAS) in postoperative days, drainage, and lengths of stay (LOS) were also similar between the two groups ( p  > 0.05). Conclusions: Driving pressure-guided ventilation during spinal surgery with a prolonged prone patient position may reduce the incidence of early postoperative pulmonary complications, compared with conventional protective ventilation.